THE IMPACT OF E-BANKING SERVICE QUALITY ON E-BANKING SATISFACTION AND E-BANKING LOYALTY - Singh, Rajesh Prettypal (Ultima Management : Jurnal Ilmu Manajemen, 2024)
Abstract - The usage of online payment is increasing rapidly worldwide. The increasing digitalization has led to the gradual integration of online banking services into the modern marketplace, catering to customer needs. The study aims to understand the impact of e-banking service quality on e-banking satisfaction and e-banking loyalty. Researching how e-banking satisfaction and e-banking loyalty can be achieved through e-banking service quality will help banking sectors survive in competitiveness. A quantitative methodology was used as a research design. The propositions of the study were tested using Structural Equation Modelling-Partial Least Squares (SEM-PLS). Google Form with 157 respondents was used to collect the data. The study found that there’s a positive significant influence between privacy & security, as well as a positive significant influence between website/app design with e-banking satisfaction. However, there’s no significant influence between reliability and customer service & support with e-banking satisfaction. Findings indicate that privacy & security and website/app design play a very important role in achieving customer satisfaction as it has become the basis of customers interpret and interacts with online banking. This research adds up considerably to the literature of bank marketing, and also academicians since it demonstrates the way internet banking service quality determinants predict e-satisfaction which ultimately raises the e-loyalty of users. This study contributes to the existing literature on e-banking service quality and provide valuable insights for e-banking businesses in Indonesia. Keywords: Cognitive Motivational Relational Theory (CMR); Customer Service & Support; e-Banking Loyalty; e-Banking Service Quality; e-Banking Satisfaction; Reliability; Privacy/Security; Website/App Design